2017
DOI: 10.1007/s13346-017-0393-4
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and qualitative studies investigating the translational potential of microneedles for use in the older population

Abstract: Microneedles (MNs) are a novel transdermal drug delivery platform, rapidly progressing from a substantive evidence base, towards commercialisation. As part of this transition, it is important to consider the future use of MNs by older people in order to ensure optimal therapeutic outcomes for this unique and increasing population group. This paper, therefore, considers the use of MNs by those aged over 65 years, investigating insertion parameters in ageing skin, alongside the feasibility and acceptability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Despite their mechanism of action requiring the puncture of the skin's protective stratum corneum barrier, microneedles have been shown not to cause infection, even when the skin is not pre-cleansed, whether the microneedles themselves were sterilised or not [17,31,32]. Importantly, erythema and disruption in skin barrier function caused by the initial skin puncture have also been shown to resolve quickly, generally within less than 24 h for barrier recovery and less than 7 days for erythema [1,20,21,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their mechanism of action requiring the puncture of the skin's protective stratum corneum barrier, microneedles have been shown not to cause infection, even when the skin is not pre-cleansed, whether the microneedles themselves were sterilised or not [17,31,32]. Importantly, erythema and disruption in skin barrier function caused by the initial skin puncture have also been shown to resolve quickly, generally within less than 24 h for barrier recovery and less than 7 days for erythema [1,20,21,34].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that repeat insertion into mouse skin in vivo, followed by subsequent retention for 24 h did not lead to disturbance in skin appearance, skin barrier function or biomarkers of infection, immunity, inflammation or allergy [19]. While we have already shown on numerous occasions that single applications of these MAPs cause no adverse effects in humans [1,14,16,20,21], the vital next step in translation of this technology is to now demonstrate, for the first time, the safety of repeat application, with prolonged wear, in human volunteers.…”
Section: Introductionmentioning
confidence: 98%
“…[60,61] The field of MN application is so large that no limits can be provided in principle, and probably most applications have yet to be implemented. [60,61] The field of MN application is so large that no limits can be provided in principle, and probably most applications have yet to be implemented.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies investigating perceptions surrounding MN technology have yielded positive findings with various potential end-user demographics including members of the lay public (LP), various healthcare professionals (HCPs) children and the elderly, being able to identify a number of benefits of MN technology, whilst also highlighting potential suggestions where improvements may be made [13][14][15][16]. However, there has been no study to date, that has specifically considered the views and opinions of patients with HIV, surrounding the use of MNs for drug delivery, despite the complexities of current ART.…”
Section: Introductionmentioning
confidence: 99%